UPAYA MENINGKATAN HASIL BELAJAR ILMU PENGETAHUAN ALAM MELALUI PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS GOOGLE SITES PADA PESERTA DIDIK SEKOLAH DASAR - Gitasmara, Fanny Ramdhanissa; Usman, Herlina (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
This study aims to improve students' learning outcomes in learning Science through the use of interactive learning media based on Google Sites for students in elementary school. The research method used is classroom action research using the Kemmis and Taggart model. This research is cyclical in nature which amounts to three cycles with the aim of making improvements to the problems encountered. In each cycle, action planning, action implementation, action observation, and action reflection were carried out. This research was conducted at Sukamaju 6 State Elementary School in Depok City involving fifth grade students who acted as research subjects. Techniques in collecting research data using observation results, field notes, test results, questionnaires, and documentation. As for knowing the existence of an increase in interest in learning, namely by using a questionnaire given to students, while to measure the improvement of learning outcomes a test instrument is used. This study was declared successful if 85% of students got an average score of 75. The results of the research in the pre-cycle showed the low scores of students on the Science learning so that it is necessary to improve learning and classroom action research using Google Sites.